Buddy Program for Bureaucrats: A Grassroot Movement of Bureaucrats to Make Indonesian World-Class Government - Aditya Ardiyan, Muhammad Rezky (Indonesian Association for Public Administration (IAPA), 2024)
It is hoped that a world-class government in Indonesia can be realized in 2024. One of the efforts to realize the government's vision is proven by the social movement of the Indonesian bureaucracy at the grassroots innovation level at the end of 2023. With social learning and experiential learning methods, movement amplification in the form of a buddy program can be obtained by both its resonance throughout the bureaucracy and society. Analysis of the research process experimentally with the learning methods that have been mentioned is documented and included in simple knowledge management utilizing Artificial Intelligence resources available on the Internet which can become knowledge management for all Indonesian bureaucrats. Based on empirical study through experimental results, it is proven that social movements through buddy programs in the bureaucratic sphere could untangle the tangled threads of government governance even in a small scope. The hope is that in the future, every innovation effort at the grassroots level needs to be supported and its implementation replicated as much as possible at a wider bureaucratic level and reaching the public so that innovation at the grassroots level becomes more widely useful and shows that the Indonesian bureaucracy has reached world-class level.